SÁNCHEZ WALSH, Arlene M. Pentecostals in America. (17th April 2019) - Hunt, Stephen
Abstract : SÁNCHEZ WALSH, Arlene M. Pentecostals in America. New York: Columbia University Press, 2018. 192pp. Pbk. ISBN: 9780231512220. £24.